Impact of Educational Space in Modern Information Age on Formation of the Intellectual Potential of Future Medical Workers - Nigina, Turakulova; Tuychiyevna, Razikova Lola (International Journal on Orange Technologies, 2023)
The paper conducts a study of the current state, the latest trends and problems in the field of education. A new concept of lifelong education, its prerequisites, definitions, basic principles and trends for further development are considered. The concept of intellectual potential and capital is considered, the factors influencing their development are given statistics on research and development. The most urgent modern problems in the field of education are highlighted.